Análise de patógenos orais entre indivíduos portadores de câncer gástrico e indivíduos sem câncer - OLIVEIRA, Gyselle Ribeiro de Carvalho (Universidade Federal do Pará, 2022)
The loss of teeth and lack of oral hygiene have been associated with the risk of developing gastric cancer in several populations evidenced in epidemiological studies. In this study, we quantitatively compared the proportion of oral pathogens in individuals with gastric cancer and individuals without cancer in a referral hospital in the city of Belém, Brazil. This study evaluated 192 patients with gastric cancer and 192 patients without cancer. Periodontal clinical examination was performed, and all individuals were submitted to the collection of salivary and dental biofilms. When comparing the median periodontal indexesin the gastric and cancer-free groups, it was statistically significant in the gastric cancer group compared to the probing depth of the periodontal pocket. Levels of bacterial DNA were observed in saliva and dental plaque, with a statistically significant difference between individuals with cancer and without neoplasia in all the bacteria surveyed. Significant relationships between biological agents and gastric cancer have been found in bacterial species that cause high rates of periodontal pathology and caries. The results suggest a different quantitative association in the presence of oral pathogens between individuals without cancer and patients with gastric cancer. As noted, it cannot be said that the bacteria present in the oral cavity increase the risk of gastric cancer or are aggravating factors of the disease. However, it is worth mentioning that, as it is part of the digestive system, the lack of care for the oral cavity can negatively affect the treatment of patients with gastric cancer.